Structural and gamma-ray attenuation properties of different resin composites for radiation shielding applications - Kavaz, E.; Tekin, H. O.; Zakaly, H. M. H.; Issa, S. A. M.; Kara, U.; Al-Buriahi, M. S.; Salah, S.; Matori, K. A.; Zaid, M. H. M. (Springer, 2022)
This research aims to investigate the structural and gamma shielding properties of different resin composite dental materials for medical applications. For this study, morphological structures and elemental compositions of the investigated composite samples were obtained by SEM/EDS analysis. The FTIR spectroscopy was employed to understand the bond structures of the resin composites. In addition to structural analyses, some of vital gamma radiation attenuation parameters were determined using MCNPX general purpose Monte Carlo code (version 2–6-0). The results showed that 3 M, GC, and Tokuyama composites indicated more regular and homogeneous structure. Zn, Zr, Ba, Sr, and Yb heavy elements were added in certain proportions in order to increase the radiopacity of the restorative material in the studied samples. As FTIR results were interpreted, C–O, O–H, and Si–O bonds were observed in all of the composites. Moreover, Bisco was found to be the most successful in reducing radiation intensity among the others, while Tokuyama was the least effective material to attenuate photon intensity. The elements Zn and Yb in Bisco have increased radiopacity and radiation absorption capabilities. It can be concluded that outcomes of the present investigation would be useful for ionizing radiation application in medicine especially in diagnostic imaging and radiation treatment.